Patients characteristics and prognostic implications of type 2 diabetes mellitus in heart failure with preserved, mid-rang reduced and reduced ejection fraction - Mrvošević, Marija; Polovina, Marija (Medicinski podmladak, 2021)
AbstractIntroduction: Type 2 diabetes mellitus (T2DM) is frequent in patients with heart failure (HF) and correlated with an increased morbidity and mortality. The features and outcomes of patients with and without T2DM depending on the HF type (HF with preserved: HFpEF, mid-range: HFmrEF; and reduced ejection fraction: HFrEF) are inefficiently explored.Aim: To explore the impact of T2DM on clinical features and one-year overall mortality in patients with HFrEF, HFmrEF and HFpEF.Material and methods: We conducted a prospective, observational study including patients with HF at the Department of Cardiology, Clinical Centre of Serbia, Belgrade. The enrolment occurred between November 2018 and January 2019. The study outcome was one-year all-cause mortality.Results: Study included 242 patients (mean-age, 71±13 years, men 57%). T2DM was present in 31% of patients. The proportion of T2DM was similar amid patients with HFrEF, HFmrEF, and HFpEF. Regardless of the HF type, patients with T2DM were probably older and have a higher prevalence of myocardial infarction, other types of coronary disorder or peripheral arterial disorder (all p
Keywords: Key words: heart failure, ejection fraction, diabetes mellitus, clinical features, mortality.